ESTUDOS ESTRUTURAIS DE PROTEÍNAS: INIBIDOR DE ALFA-AMILASE DE Secale cereale, GTPase YchF E ENOLASE DE Trypanosoma cruzi - Villalba, Cibeli May Arévalos (2012)
Proteins are the most abundant biomolecules in living organisms; they are present in all parts of a cell. They have different functions; their structural study is important because it brings greater insight into its functions and allows us to understand how they interact to each other and with the other molecules. Protein structures can be studied experimentally especially by the X-ray diffraction technique and computationally by homology modeling. Thus, in this work, structural studies were made with the alpha-amylase inhibitor from rye (Secale cereale), which inhibits the activity of amylase and then can be used in the treatment of Diabetes mellitus, obesity, pest control, amongst other applications. Through chromatographies, two different inhibitors could be separated, namely A2 and B2, which were crystallized, but did not show a minimum X-ray diffraction quality. Thus, a structural study was performed with data from a twinned crystal previously obtained, yet current refinement programs can now deal with such data. The structure was refined and compared with the alpha-amylase inhibitor 0.19 from wheat. Then, structural studies were also performed for the YchF GTPase and enolase from Trypanosoma cruzi; both have been studied with the possibility of being used as a target in the treatment of Chagas' disease. Initially, trials to express heterologously and to purify them for crystallization trials were performed; yet those were unsuccessful, a computational work was pursued, in which alignments and homology modelling for both proteins were made. The computational work was continued for Trypanosoma cruzi enolase,in which comparisons with the Homo sapiens enolase to seek and plan inhibitors for the former, through literature and data bank searches, were made; thus, docking of these was performed, which pointed more favorable binding energies for the substrates, phosphoenolpyruvate (PEP) and 2-phosphoglycerate (PG2), for the inhibitor phosphonacetohydroxamate (PAH) and for the compound coded ZINC25695689 from the ZINC (ZINC Is Not Commercial) data bank. Also, from the experimental position of the PAH inhibitor (deposited in the PDB, code 2PTZ), the interaction energies for these searched and planned molecules were estimated,through the AMBER molecular dynamics program, and, apparently, the presence of a chlorine atom conveniently bound to the inhibitor could promote an improvement of the interaction energy.